The Impact of Fluctuating Oil Revenues on Economic Growth: New Evidence from Saudi Arabia - Natto, Sultan Yahya Abbas (International Journal of Energy Economics and Policy, 2024)
The fluctuations that occur in oil revenues are among the main reasons that lead to disruptions in economies that depend on them. Hence, this study aims to find out the impact of fluctuation in oil revenues on the economic growth for the Kingdom of Saudi Arabia during the period from 2000 to 2020. The study showed that the relationship between the fluctuations of oil revenues and economic growth may be either a positive relationship, and this relationship is confirmed in oil-exporting countries, which is the most common relationship, or a negative relationship, and this relationship is confirmed in oil-importing countries, which is the exceptional case. In order to find out the direction of this relationship in the Kingdom, the study used the application of the Autoregressive Distributed Lag Model (ARDL) model. The study concluded that the fluctuations of oil revenues has significant positive effects on the economic growth of the Kingdom of Saudi Arabia in the short and long terms. Therefore, the study recommends the need for the Kingdom to exploit these revenues in areas that achieve a return for it at the present time and in the future, in a manner that guarantees the diversification of the economy and its non-disruption when any disturbances occur in these revenues, as well as keeping part of these revenues in its sovereign fund to guarantee the rights of future generations.